Analisis Stabilitas Hasil Tujuh Populasi Jagung Manis Menggunakan Metode Additive Main Effect Multiplicative Interaction (AMMI) - S. Sujiprihati; M. Syukur; R. Yunianti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The objective of this study was to identify the stability of seven sweet corn genotypes as breeding result of Center for Crop Improvement Studies (PSPT), using Additive Main Effect Multiplicative Interaction (AMMI) method. The design was Randomized Complete Block Design (RCBD) with three replications as blocks. The genotypes used were; PSPT-C, PSPT-K, PSPT-T1, PSPST-T2, PSPT-MM, and two commercial varieties Bogor-Hi and SD-2. The genotypes were planted in four different locations which included experiment fields of IPB-Cikabayan Darmaga (250 m above sea level) and Pasir Sarongge Cipanas (1120-1200 m above sea level), Gunung Geulis Cisarua (550 m above sea level), and Cibedug Ciawi (600 m above sea level). Based on the postdictive success and predictive success methods, the model used (AMMI 2) was able to explain interaction-influenced variation as much as 85%. The genotypes found stable in four locations were PSPT-MM, PSPT-T1, Bogor-Hi and SD-2. PSPT-C was specific for Ciawi, PSPT-K and PSPT-T2 specific for Cisarua. Key words: AMMI, sweet corn, multilocation trials.